(untitled) (Bangladesh Medical Journal, 2014)
This study aimed to investigate the effect of ethanolic extract of cinnamon on hyperglycemic mice. Cinnamon extract was administered at 150mg/kg and 200mg/kg body weight in alloxan induced hyperglycemic mice and the glucose lowering effect was compared to a standard oral anti diabetic drug- glibenclamide for 28 days. The fasting glucose level was measured in serum of normal and alloxan induced hyperglycemic mice. Diabetic mice exhibited an increase in the levels of glucose. It was found that blood glucose concentration was significantly decreased in a dose-dependent manner (p<0.001) with the most of the 200mg/kg dose as compared with the control. Compared to the glucose lowering action of antidiabetic drug- glibenclamide, ethanolic extract of cinnamon also indicated significant(p<0.02) glucose lowering action on diabetic mice. It is observed that use of cinnamon extract could decrease the sugar level. Therefore, cinnamon may be used as a natural glucose lowering product for the management of diabetes. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18794 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 13-16